Effect of sensory art therapies on root canal treatment anxiety and high dental anxiety in adults: A systematic review with meta-analysis - Shuhan Guo; Xuexing Luo; Jue Wang; Guanghui Huang (PLoS ONE, 2025)
Objective Root canal treatment is one of the most anxiety-provoking procedures in dental practice. Sensory art therapies can help control patient anxiety during the procedure. This systematic review aimed to synthesize the state of knowledge in this field and to examine whether sensory art therapies can reduce state anxiety during endodontics and in patients with high levels of dental anxiety. Methods Six electronic databases, including the Cochrane Library, PubMed, Embase, Web of Science, Scopus and EBSCOhost, were searched for articles published before January 2025. According to the PICOS strategy, the inclusion criteria were as follows: (P) adult patients with root canal treatment-related symptoms, high dental anxiety or dental phobia; (I) exposure to sensory art (including art therapy targeting the five senses); (C) control group receiving conventional treatment or placebo; (O) improved clinical or psychological health outcomes; and (S) randomized controlled trials (RCTs). The risk of bias was analyzed according to the Cochrane risk of bias tool for randomized controlled trials (RoB 2). The strength of evidence of the included studies was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool. Meta-analysis of the extracted data was conducted using RevMan 5.3 software, and a fixed effects inverse variance model was used for sensitivity analysis. Results Thirteen RCTs were included in the current review. Six studies had low risk of bias, six were rated as “some concerns,” and one had a high risk of bias. Descriptive analysis showed that sensory art therapies had an effect on relieving patients’ anxiety index, heart rate and blood pressure. The outcome indicators STAI-S, VAS, HR, SBP and SC were significantly improved in both the random and fixed effect models (P < 0.05), and the results of MDAS and DBP were significant in the fixed effect model (P = 0.002 for both), which demonstrates the effectiveness of SAT in reducing state anxiety and physiological stress responses. GRADE analysis presented a very low to high certainty of evidence. Conclusion Given the quality of evidence ranging from very low to high, sensory art therapies (SAT)—which includes modalities such as audiovisual resources, music, yoga, aromatherapy, and virtual reality—may offer a cost-effective and non-invasive method to alleviate physiological stress responses and reduce state anxiety during dental treatment. Further well-designed randomized controlled trials are needed to determine its clinical efficacy. Clinical relevance This systematic review and meta-analysis included 13 studies, providing low-quality evidence. Dental care professionals may consider using sensory art therapies to help reduce patients’ anxiety during dental procedures.